Appilaction On Spiral Design. - Yahaya, S.H.; Md. Ali, Jamaludin (2005)
In this paper, we introduce a G2 planar cubic transition curve by using Habib's approach. This approach purposed in 2002 where the parameters are more complete and easier to read.